أنماط إدارة المناقشات الإلكترونية القائمة على استراتيجية توليد الأسئلة في بيئة الحوسبة السحابية وأثرها في مهارات الفهم العميق وقوة السيطرة المعرفية لطالبات تكنولوجيا التعليم وآرائهن نحو إدارة المناقشات - ربيع، أنهار علي الإمام (الجمعية المصرية لتكنولوجيا التعليم, 2021)
يهدف البحث الحالي إلى تصميم نموذج للمناقشات الإلكترونية القائمة على استراتيجية توليد الأسئلة، بنمطين لإدارة المناقشات (الطالبات - المعلم)، في بيئة الحوسبة السحابية، والكشف عن أثرها في مهارات الفهم العميق، وقوة السيطرة المعرفية، لطالبات تكنولوجيا التعليم، والكشف عن آرائهن نحو إدارة المناقشات، وقد تم ذلك من خلال تصميم نموذج المناقشات الإلكترونية القائمة على استراتيجية توليد الأسئلة، بنمطي الإدارة، في بيئة الحوسبة السحابية، باستخدام نموذج عبد اللطيف الجزار (٢٠١٤ م) للتصميم التعليمي، وذلك في ضوء المعايير التصميمية، التي تم تحديدها بواسطة الباحثة. وتمثلت أدوات البحث في اختبار مهارات الفهم العميق، ومقياس قوة السيطرة المعرفية، واستبانة الآراء نحو إدارة المناقشات. وتكونت عينة البحث من عدد (١٦) طالبة، من طالبات الفرقة الرابعة شعبة تكنولوجيا التعليم بكلية البنات- جامعة عين شمس، للعام الجامعي ٢٠١٨- ٢٠١٩ م، حيث تم تقسيمهن إلى مجموعتين تجريبيتين؛ الأولى، المناقشات التي تقودها الطالبات، والثانية، المناقشات التي يقودها المعلم. وكشفت النتائج عن عدم وجود فروق دالة إحصائيا بين المجموعتين التجريبيتين، في التطبيق البعدي لكل من؛ اختبار مهارات الفهم العميق ككل، ومهاراته الخمسة كل على حده، ومقياس قوة السيطرة المعرفية، ووجود فروق دالة إحصائيا بين التطبيقين القبلي والبعدي، لاختبار مهارات الفهم العميق ككل، ومهاراته الخمسة كل على حده، والمتمثلة فيء طبيعة التفسيرات، اتخاذ القرار، طرح الأسئلة، الطلاقة الفكرية، التنبؤ، ومقياس قوة السيطرة المعرفية، لصالح التطبيق البعدي، وذلك في كل من المجموعتين، كما كشفت النتائج عن تحقيق النموذج المقترح، حجم تأثير كبير علـى مهارات الفهم العميق ككل، ومهاراته الخمسة كل على حده، وقوة السيطرة المعرفية، وذلك في كل من المجموعتين، كما أتضح عدم وجود فرق دال إحصائيا بين متوسط درجات طالبات المجموعتين التجريبيتين، في التطبيق البعدي لاختبار مهارات الفهم العميق ككل، ودرجة التمكن ٨٥% من الدرجة الكلية للاختبار، وأخيرا كشفت النتائج أن ٦٩% من طالبات عينة البحث يفضلن أن تكون المناقشات الإلكترونية تحت قيادة أستاذ المقرر، كما رأت الطالبات في كل من المجموعتين، أن قائد المناقشة أدى بكفاءة أدواره المتمثلة في الدور؛ التنظيمي، والاجتماعي، والفكري، والفني، كما كانت آراء طالبات المجموعة التجريبية الأولى التي كانت تقود الطالبات فيها المناقشات بالتناوب إيجابية نحو قيادة المناقشات، وساهموا بالعديد من الآراء المفيدة، فيما يخص الاستعداد لقيادة المناقشة، وكيفية قيامهن بالأدوار المختلفة للقائد.
Our present research aims to design a model for electronic discussions based on questions generation strategy with its two discussions management pattern (teacher – female student) in Cloud Computing Environment, to reveal their effects on Deep Understanding Skills and Cognitive Holding Power for Educational Technology Female Students and to explore their opinions towards Discussions Management with both its patterns. This objective aim has been achieved though our design of Electronic Discussions Management model with its two patterns (teacher – female student) based on Questions Generation Strategy in Cloud Computing Environment. This design is based upon our use of Abdel Latif Elgazzar's model (2014) for educational design in light of the design standards set by the female researcher. Research's tools: we use Deep Understanding Skills test, Cognitive Holding Power Measure and a questionnaire to explore the female students` Opinions towards Discussions Management with its two Patterns. Research's sample: the research's sample consists of a number of (16) Female students at Educational Technology, college of 4th grade women Ain Shams University in the Academic year 2018 – 2019 Those Female students has been divided in to two experimental groups. One is the Female students led Discussion group. While the other is the teacher – led group. This study uses the Electronic Discussions Management model based on questions generating strategy in Cloud Computing Environment. Research's Results: The research's results showed that there are no statistically significant differences on the posttest in relation to the fifth deep Understanding Skills as a whole and each one of them individually as well as Cognitive Holding Power measure, between the two experimental groups. However, there are statistically significant differences on the fifth deep Understanding Skills as a whole and each one of them individually, namely: The explanations nature, decisions making, asking questions, cognitive fluency and prediction as wells on the Cognitive Holding Power between the pretest and the posttest and those differences tilted in favor of the posttest in both experimental groups. The research's results also showed that there is no statistically significant difference on the posttest in relation to the fifth deep Understanding Skills as a whole as well as the 85% proficiency mark out of the test`s total marks. Finally, the research's results also indicated that 69% of the female students included in the research`s sample preferred that the electronic discussions must be conducted under the auspices of the course teacher, moreover female students in both experimental groups thought that the discussions` leader efficiency played all his organizational, social, cognitive, and technical roles. The first experimental group`s female students who alternately led the discussions also expressed positive opinions towards the discussion leadership and all of them offered many useful opinions and made valuable contributions whether in relation to their readiness to lead discussion or assuming the different roles entrusted to the leader.
Keywords: طلبة الجامعة -- تكنولوجيا التعليم -- الحوسبة السحابية -- المناقشات الإلكترونية -- استراتيجية توليد الأسئلة -- الفهم العميق -- السيطرة المعرفية -- جامعة عين شمس